Position Of Children In The Distribution Of Inheritance From Incestual Marriage According To Islamic And Civil Law - Diva Pitaloka; Muhammad Havez; Joko Jumadi; Ria Wierma Putri (Universitas Internasional Batam, 2024)
Marriage is a sacred process with several legal requirements that must be obeyed when one of the conditions for the validity of a marriage is not fulfilled. Furthermore, if things contained in the prohibition of marriage, such as committing inbreeding or incest, then the marriage is considered invalid or can even be canceled by law. When a marriage is considered invalid or even annulled by law, it will have legal consequences for the position of children born from the marriage, including the position of children in inheritance. This research uses a normative legal approach method that uses doctrines and principles of law as a reference and uses primary and tertiary legal materials. From this research, it can be concluded that inbreeding or incest is considered invalid in Indonesia, so it results in the position that children born from incest relationships are illegitimate children and are also referred to as adulterous children or discordant children (civil code). In terms of inheritance, children of incest have no inheritance at all. Both Islamic and Civil Law state that children of incest only have relation to their biological mother and mother's family, while to their biological father, there are no relations at all because they have no obligation to inherit each other and only have a right to demand the necessary maintenance from their biological father asset’s